2005
DOI: 10.1038/sj.ijir.3901313
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study to optimize the dosage of trimix ingredients and compare its efficacy and safety with prostaglandin E1

Abstract: Intracavernous injection of Trimix (Tx) is indicated for patients unsuitable for prostaglandin E 1 (PgE 1 ) injection due to lack of response, pain or cost. We believe that the ideal ratio of ingredient doses in Tx is yet to be found. We postulated that increasing the doses of individual drug components in an orderly manner would convey important data on penile hemodynamic response. Such information is needed to choose an effective and less costly alternative to PgE 1 with least side effects. We set out to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
2
17
1
Order By: Relevance
“…Bechara et al (1996) reported better results with the combination than with PGE 1 alone. However, Seyam et al (2005) compared trimix using a 1-mg dose of phentolamine and different doses of papaverine and PGE 1 with a 20-g dose of PGE1, found no significant differences in hemodynamic effects, rigidity, pain, and self-satisfaction between the two drugs. However, trimix produced a longer duration of erection and more priapism than PGE 1 .…”
Section: Drugs For Intracavernosal Administrationmentioning
confidence: 97%
“…Bechara et al (1996) reported better results with the combination than with PGE 1 alone. However, Seyam et al (2005) compared trimix using a 1-mg dose of phentolamine and different doses of papaverine and PGE 1 with a 20-g dose of PGE1, found no significant differences in hemodynamic effects, rigidity, pain, and self-satisfaction between the two drugs. However, trimix produced a longer duration of erection and more priapism than PGE 1 .…”
Section: Drugs For Intracavernosal Administrationmentioning
confidence: 97%
“…Inner diameter of intracavernosal arteries (both left and right) and occasionally the peak systolic velocities (PSVs) in both arteries are then measured using the Doppler blood‐flow mode. Although recent studies claim a good predictive value of PSV measurement in this flaccid state , the universal consensus is to perform the study under pharmacologically induced erection [10–15]. For this, an ICI of a single or combination of vasoactive agents (e.g., PGE1, phentolamine, and papaverine) is administered [1–3].…”
Section: Duplex Ultrasound (U/s) Penile Blood‐flow Evaluationmentioning
confidence: 99%
“… The following parameters commonly used in vascular diagnostics for the blood‐flow quantification are useful in ED evaluation [5–16]: …”
Section: Duplex Ultrasound (U/s) Penile Blood‐flow Evaluationmentioning
confidence: 99%
“…287 Currently, tri-mix is an option for severe veno-occlusive dysfunction or in the aftermath of radical pelvic surgery. 274,288 Pain or tenderness after PGE 1 is accentuated by an underlying cavernous nerve injury; therefore, bi-mix or tri-mix would be more suitable in such patients.…”
Section: Papaverine-phentolamine-pge 1 Combination (Tri-mix)mentioning
confidence: 99%